The Effect of Managerial Commitment, Budget Quality, and Capital Budget on Participatory Budgeting - Ayu Fatimatus Zahro; Dinik Fitri Rahajeng Pengestuti (Journal of Accounting Inquiry, 2022)
Purpose: This study aims to examine the effect of managerial commitment, budget quality, and capital budget on participatory budgeting. Methodology: This study uses a quantitative approach. The research method used the Quota Sampling method. Data collection techniques using questionnaires and interviews. The object of the study was aimed at the APBKal/APBDes management team at the Community and Village Empowerment Council Special Regional of Yogyakarta. The population of this study is 392 sub-district governments in the Special Region of Yogyakarta Province. Calculation of the percentage of sample size using the Slovin formula obtained 80 respondents from 392 villages which can represent the number of existing populations. The method of data analysis used in this study is the Structural Equation Model (SEM) based on Partial Least Square (PLS) using the Smart PLS 3.0. The data analysis technique uses two test methods: the measurement method (Outer Model) and the structural method (Inner Model). Findings: This study found that managerial commitment has a positive effect on participatory budgeting. Budget quality and capital budget have a negative effect on participatory budgeting. Novelty: The researcher wanted to show the differences between this study and previous studies. First, the researcher re-examined the dependent variable in the form of participatory budgeting, which was influenced by the capital budget, then added two independent variables: managerial commitment and budget quality. In future studies, it is possible to expand the number of sampling aims to provide more complex and testable validity results. It is also expected to develop study variables that can affect the samples used by researchers in the APBKal management process in each region.   Keywords: Managerial Commitment, Budget Quality, Capital Budget, Participatory Budgeting